2003 Annual Report : Innovation, Impact, Sustainability--IFC's Commitment - International Finance Corporation (Washington, DC, 2013)
This annual report reviews the International Finance Corporation's (IFC) operations activity during FY03, a period that emphasized coordination, and mutually reinforcing efforts among World Bank Group units, particularly in pursuing private sector development in client countries. The report stresses the need for support of IFC's priorities, including emerging, and frontier markets, technical assistance, and advisory services to help improve investment climates, and small and medium enterprises. Also underscored, is the significance of IFC's presence in difficult, country environments as a central component of its development mandate, while IFC's counter-cyclical role in the face of heightened investor uncertainty, and volatility of capital flows to developing countries, is recognized, as is the Corporation's performance within the annual portfolio performance review, despite continued difficulty in the global economic environment. IFC's financial management is reviewed, and its leadership for protecting the Corporation's financial integrity, without compromising its development mandate, was commendable, though the need to maintain profitability, while increasing development impacts, is stressed. The report presents financial highlights, particularly outlining IFC's commitment to innovation, impact, and sustainability, and further identifies the period's operational, and regional outlook. The annual review also summarizes the financial and portfolio reviews, as well as technical assistance and advisory services during FY03.